The AIE‐Active Dual‐Cationic Molecular Engineering: Synergistic Effect of Dark Toxicity and Phototoxicity for Anticancer Therapy. (9th September 2021) - Ma, Yucheng; Zhuang, Zeyan; Xing, Longjiang; Li, Jianqing; Yang, Zhiwen; Ji, Shaomin; Hu, Rong; Zhao, Zujin; Huo, Yanping; Tang, Ben Zhong
Abstract: The development of anticancer therapy is significant to human health but remains a huge challenge. Photodynamic therapy (PDT), inducing the synergistic mitochondrial dysfunction in cancer cells is a promising approach but suffer from the low efficiency in hypoxic microenvironment and deep‐seated tumors. Herein, to improve the outcomes of PDT for cancer treatment, a series of red fluorophores consisting of dual‐cationic triphenylphosphonium‐alkylated pyridinium and (substituted) triphenylamine are prepared as organelle‐targeting antitumor photosensitizers (PSs) with aggregation‐induced emission characteristics. These PSs can selectively accumulate at the mitochondria or lysosomes of cancer cells with both dark‐ and photo‐cytotoxicity, making them possess excellent killing effect on cancer cells and efficient inhibition of tumor growth in living mice. This study brings about new insight into the development of powerful cancer treatment. Abstract : A series of dual‐cationic fluorophores with N + and P + group are prepared as organelle‐targeting antitumor photosensitizers (PSs) with aggregation‐induced emission activity. These PSs can selectively accumulate at the mitochondria or lysosomes with both dark‐ and photo‐cytotoxicity, thus demonstrating an excellent killing effect on cancer cells and efficient inhibition of tumor growth in living mice.